MRI BRAIN EXAMINATION TECHNIQUE IN BRAIN TUMOR AT THE RADIOLLOGY INSTALLATION OF INDRIATI GENERAL HOSPITAL SOLO BARU - Tsania, Novia Putri; Andriani, Intan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
Brain tumor is a disease characterized by the growth of abnormal cells or tissue in the brain. Brain tumors are a condition that needs to be watched out for, but tumors in this part of the central nervous system do not always lead to cancer. One examination that can be used to diagnose is an MRI brain examination.The aim of this research is to analyze the results of MRI brain examination images in cases of brain tumors from axial, sagittal and coronal sections. The method in this research is descriptive qualitative research which is used to determine the results of MRI Brain and MRS examinations in brain tumor cases.The MRI Brain contrast examination procedure in brain tumor cases at the Radiology Installation of Indriati Solo Baru Hospital has been able to establish a diagnosis using the Axial T2 sequence, DWI b-value 1000, Axial T2 FLAIR, Sagittal T1, Axial T1, Axial T2 *GRE, Cor T2, Axial T1 Fat Sat + Contrast, Sagittal T1 Fat Sat + Contrast, and Coronal Fat Sat + Contrast.